Digital dexterity: Effect and implication through the use of AI among educators in Malaysia - Khamzah, Nor Ahmad; Hamid, Mohamad Ikmal; Mohd Yunus, Alwi; Abd. Aziz, Nor Erlissa; Seman @ Kamarulzaman, Mohd Ridwan (Journal of Islamic, Social, Economics and Development, 2026)
The rapid advancement of Artificial Intelligence (AI) in the education sector has intensified the urgency to strengthen digital competencies among educators. In this context, digital dexterity the ability to adapt, continuously learn, and innovate using digital technologies has emerged as a critical skill for navigating the demands of 21st-century education. This article explores the role of digital dexterity in the age of AI, with a specific focus on Malaysian educators, and examines both the effects and implications of AI integration in the teaching profession. The effects of AI implementation are multifaceted. Positively, AI enhances pedagogical practices through automation, intelligent tutoring systems, and data-informed decision-making. It supports real-time tracking of student progress, facilitates differentiated instruction, and improves the efficiency of classroom management and administrative tasks. However, the unintended effects include overreliance on algorithms, diminished educator autonomy, and widening digital gaps among educators with varying levels of technological proficiency. The implications of these effects are profound. On a professional level, educators must reconceptualize their roles not merely as content deliverers but as facilitators, data interpreters, and ethical decision-makers in technology-rich environments. Institutionally, there is a need for responsive policy frameworks and systematic capacity-building efforts to ensure that AI tools are used responsibly and equitably. This article, based on conceptual analysis and a review of current literature, outlines key strategies to develop AI-ready educators, including structured training programs, policy alignment, and the establishment of a robust digital competency framework. The findings and recommendations aim to inform educational leaders, teacher training institutions, and policymakers in creating a responsive, inclusive, and future-proof educational ecosystem.